Triclosan and its derivatives as antimycobacterial active agents - Vosátka, Rudolf; Krátký, Martin; Vinšová, Jarmila (European journal of pharmaceutical sciences, 2018)
Tuberculosis (TB) represents one of the leading causes of morbidity and mortality worldwide. Development of new potential drugs is essential because of the existence of latent TB and expansion of drug-resistant TB forms (multidrug-resistant and extensively drug-resistant tuberculosis). Triclosan is a widely used broad-spectrum biocidal agent. It has been shown to inhibit InhA, an essential enoyl acyl carrier protein reductase, resulting in the lysis of Mycobacterium tuberculosis. Triclosan can be considered as a promising compound for the inhibition of InhA and suppression of mycobacterial growth, because this polychlorinated molecule doesn't require any activation and it is able to affect the function of InhA directly. This approach enables to circumvent resistance to isoniazid. The aim of this review is to describe current knowledge about triclosan and its analogues as potential antimycobacterial agents.
Keywords: Drug Resistance, Bacterial; InhA; bakteriální léková rezistence; triclosan; Enzyme inhibition; Animals; Humans; Triclosan; Antitubercular Agents; Structure-activity relationship; lidé; Tuberculosis; antituberkulotika; zvířata; Mycobacterium tuberculosis; tuberkulóza; Diphenyl ether; Antitubercular activity